Anti-breast cancer properties and toxicity of Dillenia suffruticosa root aqueous extract in BALB/c mice - Latifah Saiful Yazan; Yong Sze Ong; Nur Elena Zaaba; Razana Mohd Ali; Jhi Biau Foo; Yin Sim Tor (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To determine the anti-breast cancer activities and the safety oral consumption of Dillenia suffruticosa root aqueous extract (DRAE) in BALB/c mice. Methods: In the anti-breast cancer study, female BALB/c mice were divided into five groups (n = 12), which were (1) positive control (with breast cancer, untreated), (2) negative control (without breast cancer, untreated) and other three groups of mice with breast cancer treated with 1000, 500 and 250 mg/kg of DRAE, respectively, by oral gavage for 28 days. All mice except from the negative control group were injected into the mammary fat pad with 4T1 cells (1 × 105 4T1 cells/0.1 mL of phosphate buffer solution). DRAE was administered orally on Day 11 after the tumor has developed. Results: The tumor volume of the 1000 mg/kg of DRAE group reduced significantly compared to the positive control while treatment with 500 mg/kg of DRAE had significantly inhibited metastasis to the heart. In the acute toxicity study, treatment with up to 5000 mg/kg of DRAE was not toxic to the animals, indicating its safety when a large amount of this plant extract was ingested. Based on the sub-acute toxicity study, treatment of the highest dose of DRAE (1000 mg/kg) had mild liver toxicity indicated by mild focal hemorrhage. Conclusions: DRAE possesses anti-breast cancer properties but at the same time it shows mild toxicity to the liver. The non observable adverse effect dose for DRAE is 500 mg/kg.